Bailing capsule (Cordyceps sinensis) ameliorates renal triglyceride accumulation through the PPARα pathway in diabetic rats - Zhang, Qian; Xiao, Xinhua; Li, Ming; Yu, Miao; Ping, Fan (Frontiers in Pharmacology, 2022)
Diabetic nephropathy (DN) is a severe diabetic complication of the kidney and is the main cause of end-stage kidney disease worldwide. Cordyceps sinensis (C. sinensis) is not only a traditional Chinese medicine (TCM) but also a healthy food. In China, C. sinensis has been widely used to treat various kidney diseases. Bailing Capsule, which active ingredient is C. sinensis, is approved to treat kidney disease, respiratory disease, and immune disease. However, its underlying mechanism in DN remains unclear. The purpose of the present study was to investigate the underlying mechanism of Bailing Capsule on kidney in diabetic rats. The DN model was established by streptozotocin (STZ) injection. Low and high doses of Bailing Capsule were orally administrated for 12 weeks after diabetes induction. Renal function was evaluated by serum creatinine, blood urea nitrogen, 24-h urinary protein, and urinary albumin. Mesangial matrix expansion and renal fibrosis were measured using histopathology staining. We found that the disorder of renal function and pathology in DN rats was significantly modified by Bailing Capsule treatment. Consistently, Bailing Capsule markedly alleviated DN rat glomerulosclerosis, tubulointerstitial injury and renal fibrosis as shown by pathological staining. Moreover, Bailing Capsule significantly reduced the kidney triglyceride content and renal lipid droplet formation in DN rats. The renal transcriptome revealed that Bailing Capsule-treated kidneys had 498 upregulated genes and 448 downregulated genes. These differentially expressed genes were enriched in the peroxisome proliferator activated receptor (PPAR) pathway and fatty acid metabolism function ontology. mRNA and protein expression analyses revealed substantial enhancement of the lipolysis pathway and inhibition of lipogenesis in Bailing Capsule-treated rat kidneys compared to DN rats. Bailing Capsule activated the inhibition expression of PPARα (peroxisome proliferator activated receptor alpha), ACOX1 (acyl-CoA oxidase 1), and SCD (stearoyl-CoA desaturase) in diabetic nephropathy while suppressing the expression of FASN (fatty acid synthase). In conclusion, Bailing Capsule could attenuate renal triglyceride accumulation in diabetic rats by activating moderating PPARα pathway.